DGI-007 Analysis of the Prescriptions of Antibiotics as Last Resort. (12th March 2013) - Charuel, A; Salles, J; Guyot, P; Legrand-Thapthimdoem, M
Abstract : Background: The composite index on proper use of antibiotics (ICATB) includes surveillance of the ATBs used, evaluation of ATB prescriptions and the existence of an ATB list associated with checking dispensing with limited duration. Purpose: To examine the conformity of ATBs as last resort prescriptions and to promote their proper use. Materials and Methods: 1988 prescriptions emanating from 7 units were investigated between 2009 and 2011, by taking into account 7 criteria: re-evaluation of the need to continue the treatment, conformity with administrative (AR), clinical/biological (CR), pharmaceutical (PR) requirements, the relevance of the prescription, the number of phone calls made by pharmacists to physicians and the number of changes made after these phone calls. Results: In 2011, prescriptions were re-evaluated in 69% of the cases, with a statistically significant increase (p < 0.01) between 2010 and 2011. Compliance with the AR was 75%, CR was 86%, the PR was 72% and the relevance of the prescription reached 70%. Compliance with these last criteria increased in 2010, but decreased again in 2011. 15% of the prescriptions required a phone call, of which 47% were followed by a change in the prescription. Conclusions: The continuation of ATB treatment requires re-evaluation according to the antibiogram or the clinical evolution. The improvements achieved in 2010 in prescription conformity and in the proper use of ATBs as last resort can be attributed to the distribution of the guide to proper use of anti-infectious drugs and changes in the presentation of prescriptions. Nevertheless, the significant decrease in 2011 requires physicians who are prolific prescribers to be sensitised. The active involvement of pharmacists in the anti-infectious drugs committee contributes to promoting the proper use of ATBs. Pharmacists called less than last year but their phone calls were more targeted and relevant. No conflict of interest.